2009
DOI: 10.3162/036298009788314336
|View full text |Cite
|
Sign up to set email alerts
|

Legislative Oversight and the Substantive Representation of Black and Latino Interests in Congress

Abstract: When determining whether or not legislators are representing their constituents' interests, scholars using voting studies may overstate the role of strategic factors, such as reelection goals and constituent influence, while understating the effect of descriptive characteristics. I argue that race and ethnicity matter in congressional oversight of bureaucratic policymaking. My examination of hearing transcripts from the 107th Congress indicates that minority legislators are more likely than white legislators t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
65
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 90 publications
(65 citation statements)
references
References 42 publications
0
65
0
Order By: Relevance
“…Building on the existing literature (Minta 2009;Rouse 2013;Wallace 2014), this project presents new evidence of how political network activity yields varying levels of substantive representation. While district demographics and partisanship have been found to be predictors of Latino legislator behaviors (Wallace 2014), the findings suggest that political networks are also closely tied to specific issue prioritization of Latino representatives.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Building on the existing literature (Minta 2009;Rouse 2013;Wallace 2014), this project presents new evidence of how political network activity yields varying levels of substantive representation. While district demographics and partisanship have been found to be predictors of Latino legislator behaviors (Wallace 2014), the findings suggest that political networks are also closely tied to specific issue prioritization of Latino representatives.…”
Section: Discussionmentioning
confidence: 99%
“…In other words, the candidates that emerge should prioritize and advocate on behalf of issues that their group supporters consider to be important. While the literature has found that Latino candidates substantively represent their constituents through formal and informal behaviors (Minta 2009;Rouse 2013;Wallace 2014) no work has investigated what role groups and elites play in shaping Latino substantive representation. This paper extends prior work in this area and argues that political network activity shapes the type of substantive representation of the winning candidates in these majority-Latino districts, given how influential the groups are to the success of some candidates over others.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 3 more Smart Citations